Female sex inversion as a reason for an unbalanced sex ratio in the neotropical species Brycon orbignyanus - Quirino, Patricia Postingel [UNESP]; Delgado, Maria Luiza Ribeiro [UNESP]; Gomes-Silva, Luciane [UNESP]; Benevente, Cristiane Fernanda [UNESP]; Grigoli-Olivio, Maiara Luzia [UNESP]; Bianchini, Bárbara Correa [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Hindawi, 2022)
The objective of this study was to temporally identify sex differentiation to morphologically characterize the formation of female and male germinal epithelium and verify the occurrence of the sex disproportion reported for this species in aquaculture. Specimens of Brycon orbignyanus cultivated in water recirculation systems with a constant temperature of 27 ± 0.5°C were used. Monthly samplings of B. orbignyanus (n = 15) were performed from two months of age until 1 year of age, and posteriorly isolated sampling was performed on specimens of two and three years of age. The gonads of the specimens were removed and processed for light microscopy. In the beginning, the undifferentiated gonads develop into ovaries (females; at three months of age) and functional testicles (primary males; at five months of age); however, some of the females go through a sex inversion process creating intersex individuals and posteriorly secondary males (at five months of age). Due to the processes of sex inversion and gonadal remodelling, the population sex proportion fluctuates until it is finally established at 1♀:2♂. Females above 15 cm are differentiated, while in males (primary and secondary), differentiation will only occur after the animal reaches 20 cm. At the end of the first year of age, primary males and secondary males reach sexual maturity, while female sexual maturity is only observed at three years of age.
Keywords: germline epithelium; gonadal differentiation; histology; oogenesis; sex inversion; spermatogenesis